Increased risk of testosterone deficiency is associated with the systemic immune-inflammation index: a population-based cohort study - Li, Yongchao; Liu, Minghui; Cui, Yu; Zhu, Zewu; Chen, Jinbo; Zeng, Feng; Gao, Meng; Li, Yang; Huang, Fang; Chen, Hequn (Frontiers in Endocrinology, 2022)
Purpose: This study aimed to explore the relationship between serum testosterone levels and systemic immune-inflammation index (SII). Methods: Complete SII and serum testosterone data of men over 20 years of age were retrieved from the 2011–2016 National Health and Nutrition Examination Survey to conduct a prevalence survey. To calculate SII, the platelet count was multiplied by the neutrophil-to-lymphocyte count ratio. Isotope dilution liquid chromatography and tandem mass spectrometry were employed to measure serum testosterone concentration. Testosterone deficiency (TD) was defined as a serum testosterone level≤300ng/dl. Weighted proportions and multivariable regression analyses were used to analyze the association between SII and TD. Results: Overall, the data of 7389 participants were analyzed, The SII ranged from 1.53 - 6297.60. Of the participants, 28.42% had a low serum testosterone level (≤ 300 ng/dl). In the fully adjusted multivariable logistic model, the second quartile (OR: 1.27, p = 0.0737), the third quartile (OR: 1.43, p = 0.0090), and the fourth quartile (OR:1.48, p = 0.0042) of SII significantly increased the TD incidence rate, with the lowest quartile of the SII as a reference. For subgroup analysis, statistically significant associations were observed in participants aged 20-40, obese, non-hypertensive, and non-diabetic. The interaction test revealed no significant effect on this connection. Conclusions: There was a positive relationship between a high SII and an increased prevalence of TD in a nationwide sample of adult men in the United States. Further prospective studies on a larger scale are warranted to confirm the causality between SII and TD.